Jacob Schieffelin papers - Schieffelin, Jacob, 1757-1835.
Legal document (1800 September 3) signed by Schieffelin regarding the son of one of his slaves; and biographical material, newspaper clippings, and other papers relating to Schieffelin's service in the British army as secretary to Governor Henry Hamilton and imprisonment in Williamsburg, Va., during the Revolution.
In part, positive and negative photocopies and typewritten transcript.
British army officer; later a pharmacist in New York, N.Y.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Hamilton, Henry, -- -1796.; Great Britain. -- Army -- Officers; Slaves -- New York (State) -- New York; United States -- History -- Revolution, 1775-1783 -- British forces; United States -- History -- Revolution, 1775-1783 -- Prisoners and prisons; Virginia -- History -- Revolution, 1775-1783.; Williamsburg (Va.) -- History -- Revolution, 1775-1783.; Army officers, British; Pharmacists